SIMULATION OF TRAIN TICKET BOOKING PROCEDURES AT XYZ TRAIN STATION BASED ON 3D ANIMATION WITH THE POSE TO POSE METHOD - Hariani, Siti; Dafitri, Haida; Usman, Ari (Journal of Mathematics and Scientific Computing With Applications, 2021)
The development of the world of technology today has almost touched all aspects of human life from the agricultural, health, academic, trade and transportation sectors. Rail transportation is one of the land transportation that plays an important role for the development of all sectors in Indonesia. However, so far there are still many people who do not understand the procedure for ordering train tickets, so the author makes a simulation education of train ticket ordering procedures that can be accessed by the general public. To realize this, it can be done by utilizing multimedia facilities based on 3-dimensional (3D) animation. The selection of multimedia facilities based on 3D Animation is also an innovation in conveying information digitally. This animation provides a detailed and structured explanation of the procedure for booking train tickets at XYZ station. This animation is made in the form of video, has an explanation in the form of text and sound. Transition effects along with background music sync are also added to make the Animations more interesting. The results of the research conducted by the author can be seen based on the results of a video simulation trial of the 3D animation-based train ticket ordering procedure that the author made in the form of a questionnaire taken from twenty respondents. From the results of the questionnaire, 85% of respondents stated that it was "very helpful", 10% "helped", and 5% "enough" that this simulation video of the train ticket ordering procedure helps people who do not understand the procedure for ordering train tickets. In addition, 85% of respondents stated that they were "very able" and 15% said "can" that 3D animation can be used in delivering education, especially education on simulation of train ticket ordering procedures that can be accessed by the general public.